(untitled) (Docentes 2.0 Journal, 2022)
The transcendental practices in the use of emerging technologies are virtual ecosystems in the educational field, by guaranteeing the creation of an immersive environment of interaction and multisensory linked to multi-user online applications, which generates events with extraordinary technological developments on the Internet. The purpose of the argumentative essay was to address reflections on the characteristics and influence that 3D tools play in the teaching/learning process. The inquiry was structured in two (2) large formal sections: the first was emerging disruptive technological trends that include technologies, mobile devices, as well as the generation of innovative digital training scenarios, and the second described virtual worlds as multisensory tools from the incidence of the potential offered by the incipient scenario of virtual reality, as training resources in the cyberculture of education. The writing was carried out under the interpretive paradigm supported by the qualitative methodological perspective; by means of the technique of reading through a heuristic calculation. Likewise, an exhaustive review of printed and digital sources was used, such as: books, magazines, dictionaries, theses, online newspapers, web pages, management of audiovisual documents, illustrations, videos, among other types of recordings. Finally, the question was raised: To what extent does the metaverse influence the teaching/learning process based on the context of virtual education? Revealed throughout the development of the investigation by combining the keywords.